Mental health and itch in burns patients: Potential associations - McGarry, Sarah; Burrows, S.; Ashoorian, T.; Pallathil, T.; Ong, K.; Edgar, D.; Wood, F. (Pergamon Press, 2016)
© 2016 Elsevier Ltd and ISBI. All rights reserved. The purpose of this study was to investigate the relationship between mental health and self-reported itch in patients with burns across a 6 month time period and to test the hypothesis that poorer mental health outcomes are associated with increased severity of itch. Method A quantitative study with three time points for data collection was conducted. Participants (232) completed assessments at 1 month, 3 months, and 6 months after burn injury. The Patient and Observer Scar Assessment Scale (POSAS) was used to report itch and the Short Form Health Survey (SF-36) provided an assessment of mental health across time. Only data from the itch and mental health subscales were used in the analysis. To analyze the data a quantile regression model was used. Results Mental health is significantly associated with itch after adjusting for variation in itch over time (p = 0.001). The regression coefficient indicates that as mental health increases by one unit, itch decreases by 0.03. Of importance, the relationship remained significant after adjusting for total burn surface area (p < 0.001). Conclusion These findings suggest there is a relationship between mental health and itch. Given the powerful impact itch can have on an individual's wellbeing health professionals can begin to further investigate itch from a bio-psychosocial perspective. Further research to investigate causal relationships between mental health and itch is important.